Graphene modified cement-based coating for heavy corrosion prevention and application

By combining silicate cement, graphene and modified epoxy self-healing resin in heavy anticorrosion coatings, the composite system is constructed using the Diels-Alder reaction, which solves the problems of high cost and insufficient durability of existing coatings, and achieves efficient corrosion prevention and self-repair performance, suitable for steel structure protection in harsh environments.

CN119192890AInactive Publication Date: 2024-12-27HUNAN JINYANG GRAPHENE RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411649867.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing heavy anticorrosion coatings have high cost, insufficient durability and difficult construction, which limit their wide application in the field of heavy anticorrosion, especially in harsh environments.

Method used

Using silicate cement as the substrate, combined with graphene and modified epoxy self-healing resin, a composite system is constructed through Diels-Alder reaction to realize the photothermal conversion and self-healing function of the coating, forming a multi-level and multi-mechanical protection system. , significantly enhance the self-healing and anti-corrosion properties of the coating.

Benefits of technology

It significantly extends the service life of the coating, improves UV resistance and weather resistance, reduces maintenance costs, simplifies construction processes, and is suitable for harsh environments such as outdoor steel structures, ships and offshore platforms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192890A_ABST
    Figure CN119192890A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene modified cement-based coating for heavy corrosion prevention and application thereof, the cement-based coating is composed of a component A and a component B. The component A comprises Portland cement, wollastonite powder, graphene and cellulose, and the component B comprises modified epoxy self-repairing resin, a dispersing agent, a water reducing agent, a defoaming agent and water. According to the graphene modified cement-based coating provided by the invention, the firmness of Portland cement, the excellent performance of graphene and the intelligent characteristic of an epoxy modified self-repairing material are fused and cooperated, so that the obtained coating has excellent adhesive force, excellent weather resistance and excellent durability, a high-efficiency anti-corrosion and self-maintenance protection system is constructed, and the service life of the coating is prolonged. And the service life of a coated facility is obviously prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a graphene-modified cement-based coating for heavy-duty corrosion protection and application thereof, belonging to the technical field of cement-based anticorrosive coatings. Background Art

[0002] With the acceleration of the global industrialization process, infrastructure construction such as bridges, storage tanks, offshore engineering and other equipment are facing increasingly severe corrosion challenges. Metal corrosion not only affects the performance and life of equipment, but also brings huge economic losses and safety risks. Especially in the fields of steel structures, bridges, storage tanks, offshore engineering, etc., the anti-corrosion protection of equipment has become a key issue that needs to be solved urgently. According to statistics, China's annual losses due to metal corrosion are as high as trillions of yuan, highlighting the urgency and high demand for the development of efficient and durable heavy-duty anti-corrosion coatings. Although traditional anti-corrosion coatings have good anti-corrosion properties, the coating is thin, the cost is high, the impact resistance is weak, and it is easily affected by ultraviolet rays and weathering, which limits its application effect in harsh environments. Breakthroughs in new materials and new technologies are urgently needed.

[0003] At present, the coatings that solve the problem of heavy corrosion protection mainly include epoxy resin coatings, polyurethane coatings, zinc-rich primers and fluorocarbon coatings. Epoxy resin coatings are widely used in the field of heavy corrosion protection due to their excellent adhesion and chemical resistance, but their curing cycle is long and their UV resistance is poor. Polyurethane coatings have good wear resistance and flexibility and are suitable for dynamic load environments, but their cost is relatively high. Zinc-rich primers rely on the sacrificial anode effect of zinc to provide corrosion protection, but the high zinc content leads to increased costs, and the consumption of zinc reduces the long-term anti-corrosion effect. Fluorocarbon coatings have excellent weather resistance, but they have disadvantages in cost and construction difficulty.

[0004] Patent document CN106189719A discloses a graphene anticorrosion coating and a preparation method thereof. The conductivity of the coating is enhanced by adding graphene to achieve cathodic protection, but the problems of UV resistance and weather resistance are not fully solved. Although zinc and aluminum have a negative electrode potential difference compared to iron, they are first corroded to form oxides, which play a role of cathodic protection, but the zinc and aluminum in the coating will eventually be consumed, making it difficult to achieve long-term corrosion protection. In summary, although the existing heavy-duty anticorrosion coatings have their own advantages, they generally have problems such as high cost, insufficient durability, and difficulty in construction, which limit their wide application in the field of heavy-duty anticorrosion. Summary of the invention

[0005] In view of the defects existing in the prior art, the first purpose of the present invention is to provide a graphene-modified cement-based coating for heavy-duty corrosion protection, which cleverly combines the firmness of silicate cement with the shielding property of graphene and the intelligent properties of epoxy-modified self-healing materials. Silicate cement forms a stable base, and graphene greatly improves the thermal conductivity and anti-corrosion performance of the coating; its unique photothermal conversion ability is combined with epoxy-modified self-healing materials, and the light-activated self-healing function is achieved through chemical modification. Even if the coating is damaged, it can be quickly repaired under light to ensure long-term anti-corrosion effect. The three work together to build a highly efficient anti-corrosion and self-maintaining protection system, significantly extending the life of the coated facilities.

[0006] The second purpose of the present invention is to provide an application of a heavy-duty anti-corrosion graphene-modified cement-based coating, which is used for surface corrosion protection of steel products such as outdoor steel structures, ships, offshore platforms, offshore wind power plants, etc., showing excellent anti-corrosion performance, effectively resisting erosion from harsh environments, and significantly extending the service life of steel products.

[0007] In order to achieve the above technical objectives, the present invention provides a heavy-duty anti-corrosion graphene-modified cement-based coating, which is composed of two-component materials A and B, wherein the mass ratio of component A to component B is 1-2:1; the mass parts of each raw material in component A are: 55-75 parts of cement, 20-40 parts of wollastonite powder, 1-10 parts of graphene, and 1-10 parts of cellulose; the mass parts of each raw material in component B are: 25-63 parts of modified epoxy self-healing resin, 0.5-2 parts of dispersant, 0.5-5 parts of water reducer, 0.1-0.5 parts of defoamer, and 30-75 parts of water; the modified epoxy self-healing resin is obtained by subjecting a water-based epoxy resin and 3-(2-furan)-1-propylamine to a chain extension reaction and then subjecting the water-based epoxy resin to a Diels-Alder reaction with N-phenylmaleimide.

[0008] The technical solution of the present invention utilizes the Diels-Alder reaction mechanism to construct a composite system of modified epoxy self-healing resin and graphene, achieving efficient self-healing and excellent anti-corrosion performance of the coating under light conditions. The system uses the dynamic nature of the Diels-Alder reaction to prepare and generate a modified epoxy self-healing resin containing a dynamic bond structure. The dynamic bond exhibits excellent dynamic recombination ability under light conditions, and combined with the photothermal properties of graphene, activates the rapid recombination and cleavage of the dynamic bonds in the coating, achieves automatic closure of micro-damage on the coating surface, and significantly enhances the self-healing efficiency and durability of the coating. Graphene's ultra-thin two-dimensional structure and its tightly stacked flake structure form a physical barrier that effectively isolates the penetration of moisture, oxygen and corrosive media. At the same time, graphene's unique photothermal properties promote the thermal stability of the coating and enhance the coating's anti-corrosion protective layer. The cement matrix, as the main carrier of the coating, complements the composite network formed by the modified epoxy self-healing resin and graphene, which not only optimizes the porous structure of the cement matrix and improves the coating's bonding strength and anti-corrosion properties, but also enhances the coating's mechanical strength and adaptability in complex environments through the synergistic effect of graphene and modified epoxy self-healing resin, thereby constructing a multi-level, multi-mechanism protection system.

[0009] Specifically, the photothermal sensitivity of the dynamic bonds in the epoxy modified resin generated by the Diels-Alder reaction enables the coating to rapidly reorganize its dynamic bonds under the action of light and heat, thereby achieving self-sealing of micro-damages. At the same time, by combining the photothermal effect of graphene with the self-repairing mechanism of the epoxy modified resin and the bonding and anti-corrosion properties of the cement matrix, they are jointly cured to form a coating, resulting in a system with unique self-repairing and anti-corrosion capabilities under light conditions. This significantly improves the comprehensive performance and service life of the coating, providing a revolutionary solution for the surface protection of steel products such as outdoor steel structures, ships, and offshore platforms, and demonstrating the technological advancement and application potential of composite materials in the field of corrosion protection.

[0010] As a preferred solution, the waterborne epoxy resin is a low-viscosity waterborne liquid epoxy resin or a waterborne epoxy resin emulsion, and the solid content of the waterborne epoxy resin is 40-60%.

[0011] As a preferred solution, the conditions of the chain extension reaction are: temperature of 60-120° C. and time of 5-12 h.

[0012] As a preferred solution, the conditions of the Diels-Alder reaction are: temperature of 60-120° C. and time of 1-4 h.

[0013] As a preferred solution, the mass ratio of the waterborne epoxy resin, 3-(2-furan)-1-propylamine and N-phenylmaleimide is 8-15:1:0.5-1.2.

[0014] As a preferred solution, the cellulose is one or more of polyvinyl alcohol fiber, aramid fiber and polypropylene fiber; and the defoaming agent is a polysiloxane defoaming agent and / or an organosilicon defoaming agent.

[0015] As a preferred solution, the water reducer is a naphthalene-based water reducer and / or a polycarboxylic acid high-performance water reducer; and the dispersant is one or more of BYK-161, BYK-190 and BYK-348.

[0016] As a preferred solution, the graphene sheet diameter is 5 to 20 μm. In the present invention, the appropriate graphene sheet diameter is conducive to dispersion and corrosion protection. A larger sheet diameter can be more effectively stacked in the coating to form a continuous protective layer, enhance the barrier effect of the coating, and at the same time improve thermal conductivity and thus improve self-healing performance and enhance the anti-corrosion effect. However, an excessively large sheet diameter may reduce the dispersibility of graphene in the coating, leading to agglomeration, thereby affecting the uniformity of the coating and even reducing its mechanical properties and anti-corrosion effect.

[0017] As a preferred solution, the cement is silicate cement and / or sulphoaluminate cement.

[0018] As a preferred solution, the mesh size of the cement is not less than 600 meshes.

[0019] The present invention also provides an application of a heavy-duty anti-corrosion graphene-modified cement-based coating, which is used for surface corrosion protection of steel products such as outdoor steel structures, ships, offshore platforms, and offshore wind power plants.

[0020] As a preferred solution, the film thickness used for anti-corrosion spraying on the surface of steel products is 0.5~1.2mm.

[0021] Compared with the prior art, the technical solution of the present invention brings about innovative and beneficial technical effects: 1) The core advantage of the graphene-modified cement-based heavy-duty anti-corrosion coating of the present invention lies in the synergistic effect of the modified epoxy self-healing resin and graphene constructed through the Diels-Alder reaction, which significantly enhances the self-healing ability and anti-corrosion performance of the coating. The photothermal sensitivity of the dynamic bonds in the coating is combined with the shielding effect and photothermal performance of graphene, so that when the coating is slightly damaged, it can quickly respond to light conditions, activate the self-repair mechanism, and achieve automatic closure of micro-damage on the coating surface, significantly improving the durability of the coating. At the same time, the addition of graphene optimizes the shielding performance of the coating, effectively resists the erosion of corrosive media, and combines the bonding and anti-corrosion properties of the cement matrix to construct a multi-level protection system, which provides comprehensive anti-corrosion protection for the coating and significantly improves the applicability and service life of the coating in harsh environments.

[0022] 2) The graphene-modified cement-based heavy-duty anti-corrosion coating of the present invention not only has excellent adhesion through the reasonable combination of various raw materials, but also has a salt spray performance of up to 3000 hours, excellent weather resistance, and ultraviolet artificial aging of up to 2000 hours, which is suitable for the field of heavy-duty anti-corrosion.

[0023] 3) The anti-corrosion coating provided by the present invention is obtained by mixing two components A and B. The Diels-Alder reaction is used to not only generate an epoxy modified resin with a dynamic bond structure, but also ensure the stability of the coating during the construction process and the self-repairing performance after curing. This heavy-duty anti-corrosion coating is particularly suitable for outdoor steel structures, ships, offshore platforms and other fields that have extremely high requirements for anti-corrosion performance. The improvement of its self-repairing ability and anti-corrosion performance effectively extends the service life of steel structures and reduces maintenance costs. The coating automatically repairs minor damage under the action of light, and high-efficiency anti-corrosion can be achieved without relying on the application of thick coatings. This feature simplifies the construction process, improves work efficiency and reduces construction difficulty. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Actual picture of the scratches on the steel plate during the self-repairing performance test of the anti-corrosion coating prepared in Example 1.

[0025] Figure 2 Actual picture of the steel plate tested for the self-repairing performance of the anti-corrosion coating prepared in Example 1 after being irradiated with sunlight for 1 hour.

[0026] Figure 3 Actual picture of the steel plate tested for the self-repairing performance of the anti-corrosion coating prepared in Example 1 after being irradiated with sunlight for 6 hours. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be further described below in conjunction with specific embodiments of the present invention. It should be noted that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments; these embodiments are only for a better understanding of the present invention, rather than limiting the scope of protection of the present invention.

[0028] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.

[0029] The aqueous epoxy resin used in the embodiments or comparative examples of the present invention is WinWinEP602P.

[0030] The graphene specification model used in the embodiments or comparative examples of the present invention is JY-GP50.

[0031] The silicate cement used in the embodiments or comparative examples of the present invention is 42.5 MPa and 1200 mesh ultrafine cement.

[0032] The sulphoaluminate cement used in the embodiments or comparative examples of the present invention is 42.5 MPa and has a mesh size of 1200 mesh ultrafine cement. Example 1

[0033] First, 20g of 3-(2-furan)-1-propylamine was dissolved in 100mL of dimethyl sulfoxide, and then 200g of water-based epoxy resin was added, and then heated to 50°C on a magnetic stirring heater, and stirred for 30 minutes to ensure uniform mixing. The temperature of the mixed solution was raised to 100°C and stirred for 6 hours. Then 20g of N-phenylmaleimide was dissolved in 50mL of dimethyl sulfoxide. After the chain extension reaction was completed, it was slowly added to the reaction system and continued to stir until completely dissolved, ensuring that the temperature was maintained at 80°C. The temperature of the reaction solution was raised to 90°C and stirred for 2 hours to promote the Diels-Alder reaction. Finally, the reaction solution was transferred to a rotary evaporator to remove the solvent, and a viscous solution was obtained, and 50mL of water was added to obtain a modified epoxy self-healing resin.

[0034] The raw materials of component A were weighed according to the following proportions: 66 parts of silicate cement, 28 parts of wollastonite powder, 4 parts of graphene, and 2 parts of polyvinyl alcohol fiber.

[0035] The raw materials of component B were weighed in the following proportions: 55 parts of modified epoxy self-healing resin, 1.5 parts of BYK-161 dispersant, 1 part of JF-2 naphthalene-based water reducer, 0.4 parts of Deqian Defom6500 defoamer, and 42.1 parts of water.

[0036] Component A is mixed and then added to the mixed solution of component B while stirring, and the mass ratio of component A to component B is controlled to be 1:1, so as to obtain a graphene-modified cement-based coating for heavy-duty corrosion protection. Example 2

[0037] Compared with Example 1, the only difference is that the proportions of the raw materials in component A are different, and the other conditions and steps are the same. The proportions of component A in this embodiment are: 65 parts of silicate cement, 23 parts of wollastonite powder, 10 parts of graphene, and 2 parts of polyvinyl alcohol fiber. Example 3

[0038] Compared with Example 1, the only difference is that the proportions of the raw materials in component B are different, and the other conditions and steps are the same. The proportions of component B in this embodiment are: 40 parts of modified epoxy self-healing resin, 1.5 parts of BYK-161 dispersant, 1 part of JF-2 naphthalene-based water reducer, 0.4 parts of Deqian Defom6500 defoaming agent, and 57.1 parts of water. Example 4

[0039] Compared with Example 1, the only difference is that the conditions of the Diels-Alder reaction are changed to: temperature of 70° C. and time of 4 h, and the other conditions and steps are the same. Example 5

[0040] Compared with Example 1, the only difference is that sulphoaluminate cement is used, polypropylene fiber is used for cellulose, and polycarboxylic acid high-performance water-reducing agent is used for water-reducing agent. The other conditions and steps are the same. Comparative Example 1 Compared with Example 1, the only difference is that no graphene is added to component A, and the other conditions and steps are the same. The proportions of each raw material in component A of this comparative example are: 70 parts of silicate cement, 28 parts of wollastonite powder, 4 parts of graphene, and 2 parts of polyvinyl alcohol fiber.

[0041] Comparative Example 2 Compared with Example 1, the only difference is that the proportion of each raw material in component A is different, and the other conditions and steps are the same. The proportion of each raw material in component A of this comparative example is: 54 parts of silicate cement, 28 parts of wollastonite powder, 16 parts of graphene, and 2 parts of polyvinyl alcohol fiber.

[0042] Comparative Example 3 Compared with Example 1, the only difference is that the epoxy resin is not modified, and the other conditions and steps are the same.

[0043] Comparative Example 4 Compared with Example 1, the only difference is that the mass ratio of waterborne epoxy resin, 3-(2-furan)-1-propylamine and N-phenylmaleimide is changed to 5:1:1.

[0044] The anti-corrosion coatings prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were sprayed on test steel plates. The film thickness of each sample was controlled at about 0.8 mm. The steel plate treatment and performance testing before paint film coating were carried out in accordance with the following standards. The measured results are shown in Table 1.

[0045] Salt spray test: GB / T1771-2007; Paint film adhesion: GB / T1720-2020; Anti-ultraviolet: GB / T 23987-2009.

[0046] Table 1 Test results of coating properties obtained from Examples 1 to 5 and Comparative Examples 1 to 4

[0047] As can be seen from Table 1, when an appropriate amount of graphene is added to the coating at the same time, the anti-corrosion performance and durability of the coating are significantly better than those of the comparative example 1 without adding graphene, while the performance of the comparative example 2 with excessive addition of graphene is still poor. The possible reason is that in the preparation process, it is found that there is agglomeration after adding too much graphene, which leads to poor dispersion of graphene in the coating, so that some areas cannot achieve the shielding effect, and then the anti-corrosion performance deteriorates; the comparative example 3 does not modify the epoxy resin, and the performance of the prepared coating is still poor, mainly because the coating does not contain reversible dynamic covalent bonds, and cannot self-repair the damaged area. Even with the presence of graphene, its heavy anti-corrosion performance is still not as good as the coating performance in the embodiment. ; Compared with Example 1, the only difference between Comparative Example 4 and Example 1 is that the mass ratio of raw materials in the modified self-healing resin is different. It can be seen from the table that the adhesion of the coating is significantly reduced, and the weather resistance is also poor. This is mainly because a reasonable modification ratio is adopted to form a denser network structure, which not only enhances the chemical bonding between the coating and the substrate and improves the adhesion, but also optimizes the density and continuity of the coating, making the reconnection between molecules more convenient, thereby significantly improving the salt spray resistance; while in Comparative Example 4, the mass ratio of epoxy resin is reduced, resulting in insufficient cross-linking, affecting the microstructure of the coating, weakening the adhesion of the coating, and reducing the corrosion resistance barrier effect, ultimately manifesting as poor adhesion and salt spray performance.

[0048] The self-repairing performance of the coating prepared in Example 1 was tested as follows: the painted steel plate was scratched with a utility knife. Figure 1 As shown, it was then placed under sunlight for 1 hour for recording and observation. The results are as follows Figure 2 , the state of the steel plate after continuing to be exposed to sunlight for 6 hours, such as Figure 3 shown.

[0049] From the actual picture of the steel plate tested for self-repair performance, we can see that Figure 1 The initial scratch state of the coating is shown. Figure 2 It shows that after 1 hour of sunlight exposure, the scratch edge begins to show signs of self-repair; Figure 3 It is further shown that after 6 hours of continuous light repair, the scratch area is significantly faded, proving the self-healing ability of the modified epoxy self-healing resin in the coating under light conditions. The main reason is that after the coating prepared by the embodiment of the present invention is damaged (such as scratches), it is exposed to sunlight, and the light energy stimulates the breaking and rearrangement of the dynamic covalent bonds in the resin. Under light conditions, the dynamic bond structure in the resin responds, promoting the reconnection between molecules, so that the molecules at the scratch can be rearranged and combined to fill the damaged area. After a period of light repair, the resin molecules in the scratch area have been restored to a certain extent, so that the scratches are faded or even disappear, showing excellent self-healing performance.

[0050] The above embodiments are only for better explanation of the principles and practical applications of the present invention, so that those skilled in the relevant technical field can better understand and utilize the present invention, but they are not intended to limit the patent scope of the present invention. All equivalent changes made using the contents of the present invention are within the patent protection scope of the present invention.

Claims

1. A graphene-modified cement-based coating for heavy-duty corrosion protection, characterized in that: The invention is composed of two-component materials A and B, wherein the mass ratio of component A to component B is 1-2:1; the mass parts of each raw material in component A are: 55-75 parts of cement, 20-40 parts of wollastonite powder, 1-10 parts of graphene, and 1-10 parts of cellulose; the mass parts of each raw material in component B are: 25-63 parts of modified epoxy self-healing resin, 0.5-2 parts of dispersant, 0.5-5 parts of water reducer, 0.1-0.5 parts of defoamer, and 30-75 parts of water; the modified epoxy self-healing resin is obtained by subjecting a water-based epoxy resin and 3-(2-furan)-1-propylamine to a chain extension reaction and then subjecting the water-based epoxy resin to a Diels-Alder reaction with N-phenylmaleimide.

2. The graphene-modified cement-based coating for heavy-duty corrosion protection according to claim 1, characterized in that: The conditions of the chain extension reaction are: temperature of 60-120° C. and time of 5-12 hours.

3. The graphene-modified cement-based coating for heavy-duty corrosion protection according to claim 1, characterized in that: The conditions of the Diels-Alder reaction are: temperature of 60-120° C. and time of 1-4 h.

4. The graphene-modified cement-based coating for heavy-duty corrosion protection according to claim 1, characterized in that: The mass ratio of the waterborne epoxy resin, 3-(2-furan)-1-propylamine and N-phenylmaleimide is 8-15:1:0.5-1.

2.

5. The graphene-modified cement-based coating for heavy-duty corrosion protection according to claim 1, characterized in that: The cellulose is one or more of polyvinyl alcohol fiber, aramid fiber and polypropylene fiber; the defoaming agent is a polysiloxane defoaming agent and / or an organosilicon defoaming agent.

6. The graphene-modified cement-based coating for heavy-duty corrosion protection according to claim 1, characterized in that: The water reducer is a naphthalene-based water reducer and / or a polycarboxylic acid high-performance water reducer; the dispersant is one or more of BYK-161, BYK-190 and BYK-348.

7. The graphene-modified cement-based coating for heavy-duty corrosion protection according to claim 1, characterized in that: The sheet diameter of the graphene is 5-20 μm.

8. The graphene-modified cement-based coating for heavy-duty corrosion protection according to claim 1, characterized in that: The cement is silicate cement and / or sulphoaluminate cement.

9. The application of a graphene-modified cement-based coating for heavy-duty corrosion protection according to any one of claims 1 to 8, characterized in that: Used for surface corrosion protection of steel products such as outdoor steel structures, ships, offshore platforms, offshore wind power plants, etc.

10. The application of graphene-modified cement-based coating for heavy-duty corrosion protection according to claim 9, characterized in that: The film thickness used for anti-corrosion spraying on the surface of steel products is 0.5~1.2mm.

Citation Information

Patent Citations

  • Cement-based polymers anti-corrosive paint and method for preparing same

    CN101333403A

  • Epoxy modified polymer cement anti-corrosive coating as well as preparation method and application thereof

    CN112375411A

  • Anticorrosive coating and preparation method and application thereof

    CN112920679A

  • Graphene two-dimensional nano material compounded anti-corrosion waterproof coating

    CN118206890A

  • Near-infrared light self-healing epoxy resin as well as preparation method and application thereof

    CN118755102A